AN ANALYSIS OF LANGUAGE STYLE USED BY THE MAIN CHARACTER IN MALEFICENT MOVIE - Ramadhana, Tria Rezky; Sahril, Sahril; Abdullah, Abdullah (State University of Makassar, 2025)
This study aims to analyze the language style used by the main character in the Maleficent movie by using Martin Joos theory (1967). Martin Joos theory classifies into 5 types of language style, namely frozen style, formal style, casual style, consultative style, and intimate style. This research uses a descriptive qualitative method where the main data of this research is taken from the dialog, script, and scenes of the Maleficent movie. The result of this study shows that there are 24 data that show language style which are divided into 5 language style, namely, frozen style, intimate style, formal style, consultative style, and casual style. 1 data that show frozen style, 10 data found on intimate style, 5 data found on formal style, 4 data found on consultative style, and 4 data found on casual style. The study can be concluded that from the analysis of Maleficent’s language style in the film shows how the use of different language styles helps shape the perception of the character and communicates the film’s key themes, such as power, betrayal, and redemption. Through the application of Martin Joos’ theory, it is clear that Maleficent’s language style not only reflects her complex personality, but also influences the dynamics of the story and the relationships between the characters in the film. Keywords: Language style, Movie, Maleficent